Hematopoietic Stem Cell Transplantation - Soiffer, Robert J.; Soiffer, Robert J. (Contemporary Hematology, 2008)
Remarkable developments in the field of transplantation have created opportunities to address the formidable challenges of transplantation across histocompatibility barriers, stem cell expansion, and prevention of complications and generation of graft-vs-tumor activity to eradicate residual disease. Stem Cell Transplantation for Hematologic and Other Disorders, Second Edition provides a glimpse into potential future applications of bone marrow derived stem cells in the field of cardiac repair. The updated chapters introduce the biologic underpinnings of hematopoietic cell transplantation, basic stem cell biology, immunobiology, and histocompatibility, with emphasis on indications and results of transplantation for specific diseases. Written by experts in the field, Stem Cell Transplantation for Hematologic Disorders, Second Edition provides seasoned professionals with a complete understanding of the current state of transplantation biology as well as a clear vision into the future.